An Introduction to Wael B Hallaq’s Works and Thoughts (Al-Qamar, 2019)
This article presents an introduction to the works and thoughts of Wael B. Hallaq (b. 1955), a renowned scholar of Islamic law and Islamic Intellectual history. Introducing Hallaq’s works and thoughts this study maintains that Hallaq’s is the author of dozens of scholarly articles and books and his teaching and research deal with the problematic epistemic ruptures generated by the onset of modernity and the socio-politico-historical forces subsumed by it; with the intellectual history of Orientalism and the repercussions of Orientalist paradigms in later scholarship and in Islamic legal studies as a whole; and with the synchronic and diachronic development of Islamic traditions of logic, legal theory, and substantive law and the interdependent systems within these traditions. His writings have explored the structural dynamics of legal change in pre-modern law, and have recently been examining the centrality of moral theory to understanding the history of Islamic law and modern political movements.
Keywords: Wael B; Hallaq; Introduction; works; thoughts